Investigation of genetic structure of various cat breeds by using d-loop polimorphism in turkey - Elif Yılmaz Şahin; Vahdettin Altunok; Ercan Kurar (Eurasian Journal of Veterinary Sciences)
Aim: In this study, Mitochondrial DNA (mtDNA) polymorphism between the Van cats and the other cat breeds is revealed. It is evaluated whether there is any relationship between the result of the mtDNA analyses obtained from Van cats and eye colours. Materials and Methods: Although it is studied with 65 blood samples and different methods, polymorphic of the place and inadequate information of literature lead to unreliable sample results. For this reason, 39 analyses of cats (25 Van cats, 3 Iran cats 3 Tekir cats, 7 siyam cats and 1 Ankara cat) are presented. 15 primers which is designed by ourselves and gained by some publication are experimented. The study is completed with 6 good working primers. The products of Polymerase Chain Reaction (PCR) CEQ-8000 are determined by using the System of Genetic Analysis of Beckman Coulter and sequence of sequences resoluted with capillary electrophoresis are determined. Results: Each of every Van cats were evaluated in their groups according to one eye or double eye and statistical differentiation was found (P<0.022) between groups. By looking at the data of analysis, one eye at the rate of 80.00% can be said in Van cats. In this study, the selection of 99 bç, a narrow location obtained from mtDNA sequence analysis is evaluated and in spite of a small number of samples the acquired statistical difference is significant. Conclusion: We found significant differences in this study. This should be study with more samples and a large mtDNA D-Loop region.